Science beyond the Classrooms and Laboratories: An ODL Approach - OCHONOGOR, C. E.; Mohapi, Soane (South African Journal of Higher Education, 2016)
To many, the teaching and learning of science is only achievable in the classroom and the laboratory in some cases. This notion has made many school learners and educators to abandon the teaching and learning of science or doing it haphazardly complaining that they lack the material and human resources. This paper examined the teaching of Saponification reactions in Organic Chemistry to undergraduates using special ODL strategies outside the classroom and organised laboratories. The strategies used are Skype technology and animation. The teaching involved both theory and practice and on evaluation, the learners proved to be as competent as if they taught in contact sessions. The study showed that sciences such as life science, physical science and related disciplines can be effectively taught and learnt through the ODL approach in schools, particularly at the University level.